DAMPAK KULIAH SAMBIL BEKERJA TERHADAP AKTIFITAS BELAJAR MAHASISWA DI POLITEKNIK TRI MITRA KARYA MANDIRI - Sukardi Sukardi; Lilik Hari Santoso; Eko Agus Darmadi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
nances, namely earning income to pay for education and daily needs while reducing the burdenon the family. But in some cases, sometimes studying while working affects learning activities oncampus, such as decreased motivation to learn so that the GPA is low. This study aims todetermine the impact of students studying while working on their learning activities at theTMKM Polytechnic. This study uses a quantitative analysis method with data collectiontechniques using a questionnaire on 27 students, both regular college students and studying whileworking.The results of this study are Agree that studying while working can reduce student learningmotivation with a percentage value of 59.26%. Strongly agree that studying while working canhinder students from doing assignments because of the lack of free time with a percentage valueof 76.85%. Strongly agree that studying while working has an impact on the frequent absence ofstudents in the class so that students are left behind in courses with a percentage value of 80.56%.Agree that because the learning intensity of students who work is less than optimal it can causethe achievement index of students who work to be lower than the achievement index of studentswho do not work with a presentate value of 68.51%